Glacial‐interglacial changes in central tropical Pacific surface seawater property gradients. (4th May 2015) - Lynch‐Stieglitz, Jean; Polissar, Pratigya J.; Jacobel, Allison W.; Hovan, Steven A.; Pockalny, Robert A.; Lyle, Mitchell; Murray, Richard W.; Ravelo, A. Christina; Bova, Samantha C.; Dunlea, Ann G.; Ford, Heather L.; Hertzberg, Jennifer E.; et al.
Abstract Much uncertainty exists about the state of the oceanic and atmospheric circulation in the tropical Pacific over the last glacial cycle. Studies have been hampered by the fact that sediment cores suitable for study were concentrated in the western and eastern parts of the tropical Pacific, with little information from the central tropical Pacific. Here we present information from a suite of sediment cores collected from the Line Islands Ridge in the central tropical Pacific, which show sedimentation rates and stratigraphies suitable for paleoceanographic investigations. Based on the radiocarbon and oxygen isotope measurements on the planktonic foraminifera Globigerinoides ruber, we construct preliminary age models for selected cores and show that the gradient in the oxygen isotope ratio of G. ruber between the equator and 8°N is enhanced during glacial stages relative to interglacial stages. This stronger gradient could reflect enhanced equatorial cooling (perhaps reflecting a stronger Walker circulation) or an enhanced salinity gradient (perhaps reflecting increased rainfall in the central tropical Pacific).